Aspects of classical and quantum integrable models - Retore, Ana Lúcia [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Aspects of classical and quantum integrability are explored. Gauge transformations play a fundamental role in both cases. Classical integrable hierarchies have an underlying algebraic structure which brings universality for the solutions of all the equations belonging to a hierarchy. Such universality is explored together with the gauge invariance of the zero curvature equation to systematically construct the Bäcklund transformations for the mKdV hierarchy, as well as to relate it with the KdV hierarchy. As a consequence the defect-matrix for the KdV hierarchy is obtained and a few explicit Bäcklund transformations are computed for both Type-I and Type-II. The generalization for super mKdV hierarchy is also explored. We studied symmetries and degeneracies of families of integrable quantum open spin chains with finite length associated to affine Lie algebras \hat{g} = A^{(2)}_{2n} , A^{(2)}_{2n−1}, B^{(1)}_n , C^{(1)}_ n , D^{(1)}_n whose K-matrices depend on a discrete parameter p (p = 0, ...,n). We show that all these transfer matrices have quantum group symmetry corresponding to removing the p^{th} node of the Dynkin diagram of \hat{g}. We also show that the transfer matrices for C^{(1)}_n and D^{(1)}_n also have duality symmetry and the ones for A^{(2)}_{2n−1}, B^{(1)}_n and D^{(1)}_n have Z_2 symmetries that map complex representations into their conjugates. Gauge transformations simplify considerably the proofs by allowing us to work in a way that only unbroken generators appear.The spectrum of the same integrable spin chains with the addition of D(2) n+1 is then determined using analytical Bethe ansatz. We conjecture a generalization for open chains for the Bethe ansatz Reshetikhin’s general formula and propose a formula relating the Dynkin labels of the Bethe states with the number of Bethe root sof each type.

Aspectos de integrabilidade clássica e quântica são explorados. Transformações de gauge têm papel fundamental em ambos os casos. Hierarquias integráveis clássicas têm uma estrutura algébrica subjacente que traz uma universalidade para as soluções de todas as equações que ac ompoem. Essa universalidade é explorada juntamente com a invariância da equação de curvatura nula por transformações de gauge para construir sistematicamente as transformações de Bäcklund da hierarquia mKdV, assim como para relacioná-la com a hierarquia KdV. Como uma consequência a matriz de defeito para a hierarquia KdV é obtida e alguns exemplos explícitos são calculados tanto para o Tipo-I quanto para o Tipo-II. A generalização para a hierarquia mKdV supersimétrica também é discutida. Nós estudamos simetrias e degenerecências de famílias de cadeias de spin quânticas integráveis com comprimento finito associadas a álgebras de Lie afins \hat{g} = A^{(2)}_{2n} , A^{(2)}_{2n−1}, B^{(1)}_n , C^{(1)}_ n , D^{(1)}_n cujas matrizes K dependem de um parâmetro discreto p (p = 0, ...,n). Nós mostramos que todas essas matrizes de transferências têm simetrias de grupos quânticos correspondentes a remover o nodo p do diagrama de Dynkin de \hat{g}. Também mostramos que as matrizes de transferência para C^{(1)}_n e D^{(1)}_n têm também simetria de dualidade enquanto A^{(2)}_{ 2n−1}, B^{(1)}_n e D^{(1)}_n têm simetrias Z_2 que mapeiam representações complexas em seus conjugados. Transformações de gauge simplificam consideravelmente as provas pois permitem-nos trabalhar com apenas os geradores que não foram quebrados. O espectro dessas matrizes de transferência juntamente com D^(2)_{n+1} é então calculado usando o método do Bethe ansatz analítico. Nós conjecturamos uma generalização para cadeias de spin abertas para a fórmula de Reshetikhin e propomos uma fórmula relacionando os índices de Dynkin dos estados de Bethe com o número de raízes de Bethe de cada tipo.
Aspectos clássicos e quânticos de modelos integráveis
Keywords: Física matemática; Teoria de campos (Fisica); Solitons